An Investigation of Marine Taxa Referenced in Thesis Titles and Abstracts as a Collection Development Tool. Issue 2 (3rd April 2019) - Timms, Geoffrey P.
ABSTRACT: We evaluated titles and abstracts of 372 marine biology master's theses to identify the marine taxa researched by graduate students at our institution. Of 191 species investigated since 1976, the 15 most-researched species are regionally important and have each been researched at least five times. Fisher exact tests identified taxa demonstrating statistically significant recent growth in research. A collection analysis of monographs about these species and taxa compared to four peer institutions highlighted strengths and weaknesses within our marine biology collection. This investigation demonstrates how taxonomic data in titles and abstracts can serve as a tool to guide biology collection development.